Strategic management paper: China Banking Corporation - Maceda, Jonie P. (Animo Repository, 2002)
This is a strategic management paper designed for China Banking Corporation, a compamy belonging to the financial intermediation services industry, an industry that is responsibie of meeting the financial needs of varoius parties in our economy. This paper was developed using the theoretical frameworks and concepts that I have learned in my Strategic Management course. The paper is subdivided into fice modules that will be summarized as follows: Module I. This module deals with the external environment of the company. It is in this module that the bank's industry is defined, together with the evaluation and scanning of various external factors that will serve as the basis of the opportunities and threats that the company may have to contend with. Module II. After considering the external environment in Module I, the internal environment will be covered by the second module. It is here where Chinabank will be dissected, its history, ownership, product lines, the systems and organizational set up, its financial condition and its outlook of what it will be in the future. In this module, two bases were shown to derive the strengths and weaknesses of the company. These are the value chain and the financial statement analysis. Module III. After the bases for strategy formulation have been laid down in the two preceeding modules, the visions, objectives and strategies will now be the focus of this module. Module IV. After having figured out the opportunities, threats, societal expectations, strengths and wekanesses of the bank, together with the evaluation of the bank's decision makers as well as the company's ulture which were vital in the formulation of strategies towards the realization of the bank's objectives, this module will now focus on the equally important issue, that is, the implementation od strategies that were formulated in the previuos module. The 7S framework was used in this module to check the banks capability to implement the proposed changes and strategies was tested in terms of structure, strategy, style, system, staff skills and shared values. After the process of evaluation and checking, this module showed that the bank is capable of adapting to the proposed changes given the support of the management and the total commitment of its workforce. Module V. This last module is focused on the financial projections and analysis. This is the section wherein the projected balance sheet and income statements of the bank is presented, ratios are produced to show the bank's financial condition, profitability, stability and over all performance as measured in terms of money.